The Amplatzer duct occluder (ADOII) and Piccolo devices for patent ductus arteriosus closure: a large single institution series - Bruckheimer, Elchanan; Steiner, Kristoffer; Barak-Corren, Yuval; Slanovic, Leonel; Levinzon, Michael; Lowenthal, Alexander; Amir, Gabriel; Dagan, Tamir; Birk, Einat (Frontiers in Cardiovascular Medicine, 2023)
Purpose Evaluate Piccolo and ADOII devices for transcatheter patent ductus arteriosus (PDA) closure. Piccolo has smaller retention discs reducing risk of flow disturbance but residual leak and embolization risk may increase. Methods Retrospective review of all patients undergoing PDA closure with an Amplatzer device between January 2008 and April 2022 in our institution. Data from the procedure and 6 months follow-up were collected. Results 762 patients, median age 2.6 years (range 0–46.7) years and median weight 13 kg (range 3.5–92) were referred for PDA closure. Overall, 758 (99.5%) had successful implantation: 296 (38.8%) with ADOII, 418 (54.8%) with Piccolo, and 44 (5.8%) with AVPII. The ADOII patients were smaller than the Piccolo patients (15.8 vs. 20.5 kg, p < 0.001) and with larger PDA diameters (2.3 vs. 1.9 mm, p < 0.001). Mean device diameter was similar for both groups. Closure rate at follow-up was similar for all devices ADOII 295/296 (99.6%), Piccolo 417/418 (99.7%), and AVPII 44/44 (100%). Four intraprocedural embolizations occurred during the study time period: two ADOII and two Piccolo. Following retrieval the PDA was closed with an AVPII in two cases, ADOI in one case and with surgery in the fourth case. Mild stenosis of the left pulmonary artery (LPA) occurred in three patients with ADOII devices (1%) and one patient with Piccolo device (0.2%). Severe LPA stenosis occurred in one patient with ADOII (0.3%) and one with AVPII device (2.2%). Conclusions ADOII and Piccolo are safe and effective for PDA closure with a tendency to less LPA stenosis with Piccolo. There were no cases of aortic coarctation related to a PDA device in this study.